2020
DOI: 10.37358/rc.20.1.7848
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Elevated Parathormone Levels on the Severity of Pulmonary Hypertension in Patients with End Stage Renal Disease Undergoing Hemodialysis

Abstract: One of the most severe cardiovascular complications encountered in patients with end stage renal disease (ESRD) undergoing hemodialysis (HD) is pulmonary hypertension (PH). Secondary hyperparathyroidism (SHPTH) is supposed to be one of the contributing mechanisms responsible for the occurrence of PH in these patients.The aim of our study is to determine if the elevated values of intact parathormone (iPTH) are correlated with increased pulmonary vascular resistance (PVR) in patients ESRD undergoing HD.Our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…In some studies patients with MAU showed a higher prevalence of concentric than eccentric LVH [26]. Prevalence of CKD (13.32%) of albuminuria and reduced eGFR in hypertensive patients was similar to other studies [27][28][29][30][31]. To reduce the burden of CKD and HMOD by hypertension screening programmes and by development of public primary care health strategies, lower blood pressure and risk factors, represented a priority of the present research.…”
Section: Left Ventricular Hypertrophysupporting
confidence: 81%
See 1 more Smart Citation
“…In some studies patients with MAU showed a higher prevalence of concentric than eccentric LVH [26]. Prevalence of CKD (13.32%) of albuminuria and reduced eGFR in hypertensive patients was similar to other studies [27][28][29][30][31]. To reduce the burden of CKD and HMOD by hypertension screening programmes and by development of public primary care health strategies, lower blood pressure and risk factors, represented a priority of the present research.…”
Section: Left Ventricular Hypertrophysupporting
confidence: 81%
“…LVH is an important risk factor for atrial fibrillation, diastolic and systolic heart failure, arrhythmias and sudden death [24][25][26][27]. Studies have demonstrated that concentric left ventricular hypertrophy implies the highest CV risk and that angiotensin converting enzyme inhibitors favour regression of both LVH and albuminuria [25][26][27][28]. In some studies patients with MAU showed a higher prevalence of concentric than eccentric LVH [26].…”
Section: Left Ventricular Hypertrophymentioning
confidence: 99%
“…Patients with PH had higher AVF blood flow, 1150 (1000–1410) mL/min versus 980 (892.5–1150) mL/min, p < 0.001. 12 Therefore, when the SPAP was >45 mmHg and the flow of AVF was higher. It suggested that the AVF function was better.…”
Section: Discussionmentioning
confidence: 97%
“…1 Pulmonary artery pressure (PAP) in MHD patients was significantly related to AVF blood flow. 11,12 After the establishment of AVF, the circulation returned volume and cardiac output were increased sharply, which led to an increase in PAP.…”
Section: Introductionmentioning
confidence: 99%
“…In a small prospective research of 12 patients, Yigla et al 13 showed the influence of increasing cardiac output (CO) after AVF creation on the rise of pulmonary arterial pressure (PAP). Afzal et al 11 mentioned in a recent article that among the factors contributing to the development of PH, AVF could be one of the causes of unexplained elevated PAP. Other researchers, on the other hand, discovered no link between AVF flow rates and development of PH similar to our finding.…”
Section: Discussionmentioning
confidence: 99%